Cost Effective Analysis of Supplying Essential Food Materials to Indian Armed Forces through Drone Application Versus Conventional Transport by Army Trucks - Ampu Harikrishnan, Gurprit Singh (International Journal of Intelligent Systems and Applications in Engineering, 2024)
BA stands for cost-benefit analysis. Comparative advantage analysis serves as an economic evaluation technique that quantifies the positive and negative outcomes of a particular intervention or program regarding financial worth. By assigning monetary value to all program outcomes, decision-makers can directly compare the results of various decisions. This research paper provides an overview of the Indian Army drone application, including its motivation, methodology, implementation details, and future scope. The objective of the application is to equip soldiers with the ability to choose the most appropriate drone for payload delivery tasks based on load weight, thus improving operational efficiency and effectiveness. The primary purpose of this application is to shield the tourism and hospitality sectors from the destructive effects of weapons and shelling. The drone also minimizes the impact of sending these pots, arms, and ammunition by heavy vehicles, minimizing the impact of heavy vehicles damaging hilly areas, which are prone to landslides that further damage the soil and surrounding vegetation.